Miniaturized and Bandwidth Improvement of Bandpass Filter using A Quarter Wavelength Resonator - Dwi Astuti Cahyasiwi; Amtsaluddin Zanetti; Dian Widi Astuti; Galih Adhi Yoga (LPPM Universitas Negeri Semarang, 2025)
The miniaturization of radio frequency (RF) and microwave filters is crucial in modern communication systems, particularly in space-constrained environments such as portable, wearable, or integrated multi-band platforms. In this study, a compact single band-pass filter (BPF) is proposed using an L-shaped resonator loaded with a via-through hole. The incorporation of the via allows the creation of a quarter-wavelength resonator, which significantly reduces the physical size to 44.6% compared to traditional half-wavelength resonators commonly used in band-pass filters. Additionally, the via contributes to an improved impedance bandwidth. Two L-shaped resonators are arranged in a back-to-back configuration to realize a second-order filter response. The structure is excited through a stub-loaded transmission line that couples the signal from port one to port two. To validate the proposed design, the filter was fabricated and measured. Experimental results demonstrate a -3 dB fractional bandwidth (FBW) exceeding 25% at the centre frequency of 3.2 GHz, with a measured insertion loss of -1.662 dB across the passband, indicating good performance for compact filter applications.